The Development of Reading Comprehension Ability of Grade 5 Students by using Scaffolding Learning Management. - sitthijinda, sirimas; Yeekengaem, Sariyagan; Phitchayapirath, Piyaporn (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The purpose of this research were 1) to compare the reading comprehension ability of Grade 5 students by using learning management techniques to enhance learning. Before learning and after learning 2) To study the satisfaction of Grade 5 students by organizing learning with techniques to enhance learning. The sample group used in the research was 14 Grade 5 students in the 2nd semester of the 2022 academic year at Ban Na Dun School which were obtained from Cluster Random Sampling using the lottery method. Using network schools is a random unit Research tools include learning management plans. Develop reading comprehension ability with 6 additional techniques for learning. A test to measure reading comprehension ability. It is a multiple-choice test with 4 options, 30 questions, satisfaction questionnaire. Statistics used to analyze the data include mean ( ) standard deviation (S) and t-test (Dependent Samples). The research findings were as follows: Ability to read and understand the main points of Grade 5 students by using learning management techniques to enhance learning. Learning after school is higher than before. Statistically significant at the .05 level, which is in line with the hypothesis set. The students who were taught using the scaffolding learning style were satisfied with the learning activities overall at the highest level of satisfaction.